The Impact of Cultural Similarity on Consumer Ethnocentrism Tendencies Toward Foreign Products - alshammari, eman; WILLIAMS, MICHAEL (Archives of Business Research, 2018)
Consumer ethnocentrism is found to be an important factor in making consumers adversely evaluate foreign products. This study is an attempt to improve understanding of consumer ethnocentrism and its influence on consumer attitude and purchase intention toward foreign products in an emergent market. It was also hypothesized that cultural similarity moderates the relationship between consumer ethnocentrism and purchase intention in which domestic products are not available. All but one of the hypotheses were accepted. Consumer ethnocentrism is found to have a strong influence on consumer attitude but does not significantly affect consumer purchase intention toward foreign products. Cultural similarity was found to have a significant moderating effect on the relationship between consumer ethnocentrism and purchase intention. This suggests that cultural similarity plays an important role for ethnocentric consumers in the evaluation of foreign products. Theoretical and managerial implications are discussed.